Diseño de un plan de manejo de residuos líquidos peligrosos en el laboratorio de aguas de la empresa de acueducto y alcantarillado de Bogotá incorporando la recuperación de plata metálica presente en residuos de la técnica de cloruros. (2022)
In this project, a proposal was made for a hazardous liquid waste management plan for the laboratory of the Bogotá aqueduct and sewage company, and a study was made to recover the silver contained in one of the hazardous liquid waste generated by the laboratory. , this in order to respond to the non-conformities presented by the evaluating entities and reduce the negative environmental impact generated by the mishandling of hazardous liquid waste.